Differentiation of power and endurance athletes based on their muscle fatigability assessed by new spectral electromyographic indices - Mileva, K. N.; Morgan, J.; Bowtell, J. (Journal of Sports Sciences, 2009)
The aim of this study was to differentiate between endurance and power athletes based on electromyographic (EMG) data analysed using new spectral indices. Nine endurance and six strength athletes were recruited to complete sets of knee extension repetitions (15 per set) until exhaustion, with each set followed by a maximal voluntary isometric knee extensor contraction. Peripheral muscle fatigue of the vastus lateralis, vastus medialis, and rectus femoris (bilaterally) was quantified by the changes in median frequency of the EMG power spectrum and a new spectral EMG fatigue index. Cluster analysis of the fatigue indices differentiated athletes into two groups: endurance (fatigue resistant) and strength (faster fatigue), whereas cluster analysis of the median EMG power spectrum frequency produced six indistinct groups. The average fatigue index for the quadriceps group increased across repetitions by 40 ± 24% in the endurance group and by 184 ± 12% in the strength group. The decrease in peak force and power across repetitions, and the rate of force decrease during maximal voluntary contraction per set, were significantly smaller for the endurance than for the strength group. The new spectral EMG indices effectively discriminated between strength and endurance athletes, thus providing a useful functional index that could be applied to track training adaptations as well as potentially talent identification.